(untitled) (Italian Journal of Public Health, 2009)
According to the conclusions of the World Health Organisation’s 2000 report Italy had the second best health system in the world [1] with Italians having one of the highest rates of life expectancy... However, since 2001 the 19 Italian Regions and 2 Autonomous Provinces have exercised their autonomy very differently, with Northern regions being more successful in establishing effective structures of health care delivery, management and monitoring, as compared to regions in the South. This regional variation in health care reflects (and exacerbates) differences of contextual, political, economic and cultural, factors as well as differences between regional health systems. A recent survey [2] showed that in 14 of the 21 Regions and Autonomous Provinces, the system is performing fairly well and is well perceived by citizens.